Midwives' experiences working with women and girls surviving violence in Yemen: a qualitative study - Al-Zumair, Marwah; Leegstra, Luz Marina; Zaid, Hussein; Ferrer Pizarro, Raisa; Al-Zumair, Monia; Bawahda, Lamya; Jahn, Albrecht; Maxwell, Lauren (Frontiers in Global Women's Health, 2025)
BackgroundYemeni women and girls have long endured pervasive violence, a situation further exacerbated by the ongoing humanitarian crisis. Violence against women and girls (VAWG) is strongly stigmatized in the Yemeni context. In under-resourced, rural settings like Yemen, where gender inequities prevent women and girls from accessing the formal health system, community midwives may be an important resource for women and girls who experience interpersonal violence. This study explored community midwives' knowledge, training, and applied experience working with women and girls who experience interpersonal violence.MethodsWe conducted 20 in-depth interviews with community midwives in four Yemeni governorates. A female Yemeni physician and qualitative researcher trained in the ethical conduct of VAWG-related research conducted interviews using a semi-structured interview guide. Participants gave verbal consent for participation in the one-time interview. We used thematic analysis to summarise the findings. Interviews were transcribed in Arabic and English, and differences in interpretation were resolved through consensus.ResultsWhile midwives had limited formal training in supporting women and girls who experience interpersonal violence, they play a critical role in responding to VAWG in Yemen. Community midwives provide psychological support, contraception, violence-related health care, and referrals to more advanced healthcare and protection services, including women-friendly spaces (WFSs) and shelters. Lack of training and treatment guidelines, in addition to a lack of supportive services and VAWG-related stigma, were important barriers for midwives working with VAWG. The stigma associated with sexual violence discouraged women from seeking health care or accessing limited protection services.ConclusionCommunity midwives in Yemen are well-placed to support women and girls who experience violence. Midwives should receive context-appropriate training and support to work with women and girls who experience violence. The lack of available services and the stigma associated with experiencing, reporting and supporting VAWG survivors must be carefully considered before designing any intervention.